MILITARY TRAINING OF YOUNG PEOPLE IN THE VOLUNTEER ASSOCIATIONS (1927–1941) - Moseev, V.I.; Cherenkov, V.E. (Tambov University Review. Series: Humanities, 2016)
On the basis of archive sources different aspects of the activity of the volunteer associations of Osoaviakhim (Society for Defense Assistance, Aviation and Chemical Building), Avtodor (Society for Road and Automobilism Development), ROKK (Russian Society of Red Cross), ODR (Society of Radio Friends), their contribution to the military training in young people as the integral part of strengthening the defence capability of the country are examined. Different directions of these social organizations’ activity such as moral-political, military-technical, physical training of preinduction and draft-age young people are shown. The voluntary societies had the aim set by party government of the country to start work at military-educational points, courses, in school, in camps of defence communities, in different circles, houses of defence, museums, libraries, village-reading rooms, beautiful corners and etc., to help the country in expiration of general and military illiteracy. Besides, it was necessary to rebuild the work of mass defence organizations and first of all Osoaviakhim. The main change was in differentiation of the spheres of their activity, in transmission of some functions of Defence Department to it. The necessity to rebuild was founded by the fact that the reorganisation and retrofitting of the army was necessary. And the improvement of educational-material basis of military preparation was needed. The military education control in organizations Osoaviakhim was realized by Revolutionary Military Council the USSR and Central Council of Osoaviakhim. And other organizations also participated: Avtodor organized military section, ODR prepared radio-fans, ROKK trained military-sanitary personnel for the defence interests of the country.